Plant Spacing Implications for Grafted Grapevine II Soil Water, Plant Water Relations, Canopy Physiology, Vegetative and Reproductive Characteristics, Grape Composition, Wine Quality and Labour Requirements - Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
Vitis vinifera L. cv. Pinot noir vines grafted onto rootstock 99 Richter and grown under six plant spacings (3 x 3 m; 3 x 1,5 m; 2 x 2 m; 2 x 1 m; 1 x 1 m; 1 x 0,5 m) were investigated in terms of canopy dimension and microclimate, soil conditions, canopy physiology, vegetative and reproductive growth characteristics, grape composition, wine quality and labour input. Vines were pruned to six buds/m2 soil surface and supplementary irrigated just after pea berry size and veraison stages. The number of leaf layers, light intensity and air flow generally decreased with closer spacing, whereas relative humidity increased. In contrast to the virtually stable, albeit lower, soil water content of closer-spaced vines, that of wider spacings noticeably decreased from veraison to ripeness. This may be ascribed to the almost continuous seasonal shading of the soil in the case of the narrower spacings, and the generally higher soil temperatures found for the wider spacings. Leaf and bunch water potentials of both wider- and closer-spaced vines decreased during the ripening period. Bunches were more sensitive to water stress. Leaf and bunch water potential coincided with soil water content. The lower photosynthetic activity of closely spaced vines was accompanied by increased transpirational water loss and is mainly ascribed to less favourable canopy microclimate. Despite the supplementary irrigation and slight differences in leaf water potential between spacings, wider-spaced vines apparently grew under less water stress during the ripening period. This was also evident from leaf xylem sap abscisic acid levels at ripeness. Shoot, leaf and berry growth rates apparently increased with narrower spacing, whereas total leaf area per vine decreased. Fresh berry mass of narrow-spaced vines was, however, slightly lower at ripeness. Budding of narrow spacings increased, whereas fertility and bunch mass were reduced, resulting in decreased yield per vine.  Optimum berry set and yield per hectare occurred for medium-spaced vines (2 x 2 m, 2 x 1 m); this was also evident on a m2 soil surface basis. Leaf area per fresh mass of widely spaced vines ( 3 x 3 m, 3 x 1,5 m) was much lower than the generally required 10 - 12 cm2 and points to overcropping.  Musts of widely spaced vines had less soluble solids and titratable acidity, whereas must pH increased progressively from widely to closely spaced vines. It would seem that widely spaced vines were overcropped due to low cultivar vigour and/or low yielding capacity of the soil, eventually affecting ripening. Grapes from medium-spaced vines had higher anthocyanin levels in the skin. Sensorially, wines made from closer spacings (2 x 2 m, 2 x 1 m, 1 x 1 m, 1 x 0,5 m) scored distincly higher than those from widely spaced vines. Although yield per hectare was higher, closely spaced vines (1 x 1 m, 1 x 0,5 m) needed significantly higher inputs for canopy management, harvesting and pruning. Considering land utilisation, vine performance, wine quality as well as labour input, medium-spaced vines (2 x 2 m; 2 x 1 m) performed optimally.